2007
DOI: 10.1021/jf062131a
|View full text |Cite
|
Sign up to set email alerts
|

Porosity and Its Effect on the Digestibility of Dilute Sulfuric Acid Pretreated Corn Stover

Abstract: Enzyme accessibility has been proposed as a limiting factor in the enzymatic conversion of the cellulose in biomass to glucose. Prior work has shown a strong correlation between porosity, measured as the change in the volume of pores accessible to a cellulase-sized molecule, and the initial digestibility of biomass pretreated by various methods. The goal of this work was to determine if porosity was one of the factors governing the overall enzymatic digestibility of the cellulose in dilute acid pretreated biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
0
11

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(104 citation statements)
references
References 33 publications
3
88
0
11
Order By: Relevance
“…NMR measurements conducted on these samples showed that dilute acid pretreatment increased the porosity in corn stover (Ishizawa et al, 2007), suggesting that the observed increase in T. reesei Cel7A access to the cellulose in PCS is due to improved physical access within the biomass structure. However, no measurable differences in porosity were found between these PCS samples (Ishizawa et al, 2007). Sample porosity, therefore, cannot explain the observed differences in T. reesei Cel7A accessibility between differentially pretreated corn stover samples.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…NMR measurements conducted on these samples showed that dilute acid pretreatment increased the porosity in corn stover (Ishizawa et al, 2007), suggesting that the observed increase in T. reesei Cel7A access to the cellulose in PCS is due to improved physical access within the biomass structure. However, no measurable differences in porosity were found between these PCS samples (Ishizawa et al, 2007). Sample porosity, therefore, cannot explain the observed differences in T. reesei Cel7A accessibility between differentially pretreated corn stover samples.…”
Section: Discussionmentioning
confidence: 96%
“…This concept has been discussed in the literature as relating changes in the porosity of the biomass sample to digestibility (Esteghlalian et al, 2001;Grethlein, 1985). NMR measurements conducted on these samples showed that dilute acid pretreatment increased the porosity in corn stover (Ishizawa et al, 2007), suggesting that the observed increase in T. reesei Cel7A access to the cellulose in PCS is due to improved physical access within the biomass structure. However, no measurable differences in porosity were found between these PCS samples (Ishizawa et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The smallest solutes are saccharides such as glucose (0.8 nm) (Flournoy et al 1991;Kuga 1981;Lin et al 1987;Stone and Scallan 1968a;Wang et al 2011), mannitol (0.8 nm) (Carpita et al 1979), sucrose (1.0 nm) (Carpita et al 1979;Kuga 1981;Van Dyke 1972), cellobiose (1.0 nm) (Lin et al 1987), maltose (1.0 nm) (Flournoy et al 1991;Stone and Scallan 1968a), raffinose (1.2 nm) (Flournoy et al 1991;Kuga 1981;Stone and Scallan 1968a;Van Dyke 1972), and stachyose (1.4 nm) (Carpita et al 1979;Stone and Scallan 1968a). PEGs range in size from 0.44 nm for ethylene glycol (Kuga 1981) to 13.0 nm (Lin et al 1987;Van Dyke 1972), while dextrans have been reported in the literature from 1.8 nm in diameter (Ishizawa et al 2007) up to 586 nm (Arond and Frank 1954). Figure 5 shows how the solute diameter correlates with molecular mass for both PEGs and dextrans.…”
Section: Solute Exclusion Techniquementioning
confidence: 95%
“…Fig. 5 a Diameter of dextran and PEG probe molecules as a function of molecular weight (based on data from Arond and Frank 1954;Carpita et al 1979;Day et al 1978;Flournoy et al 1991;Granath and Kvist 1967;Hill et al 2005;Ishizawa et al 2007;Kuga 1981;Lin et al 1987;Peters 1986;Stone et al 1969;Stone and Scallan 1968a;Van Dyke 1972;Wang et al 2011;Wong et al 1988). b Inaccessible cell wall water volume as a function of size of different molecular probes.…”
Section: Solute Exclusion Techniquementioning
confidence: 99%
“…O pré-tratamento com ácido sulfúrico diluído tem sido amplamente utilizado, principalmente no processamento de gramíneas, com relativo sucesso (CANILHA et al, 2011;CASTRO;HSU et al, 2010;ISHIZAWA et al, 2007;SANTOS et al, 2011;WYMAN, 2004 essas gotículas são forçadas para fora da parede celular, alterando a sua distribuição topoquímica na biomassa pré-tratada (DONOHOE et al, 2008;CHENG, 2002). A figura 9 ilustra o comportamento da lignina nessas condições.…”
Section: Parede Celular Da Cana-de-açúcarunclassified